FOREST COMPOSITION CHANGES WITH COMPETITION IN THE NORHERN PART OF TURKEY - Ibrahim Atalay (European Scientific Journal, ESJ, 2014)
Turkey, having at least three main climatic types, various land forms and altitudes changing frequently due to mountainous topography, contains more than 10 thousands plant species. The study area on northern Turkey is rich in different forest vegetation types changing from broadleaf deciduous forests to Mediterranean shrublands, and pure or mixed Pinus sylvestris var. sylvestris forests which resembles taiga forest in northern Hemisphere. Here, under the humid-mild and cold-subhumid conditions, the composition of climax forests are subjected to changes by virtue of excessive forest harvesting, improper silvicultural applications, and abandonment of agricultural fields. This structure leads to the competition for light among trees and shrubs in the Black Sea Region and its southern parts. In the humid mild climatic conditions prevailing along the coastal belt of Black Sea Region, for instance, abandoned agricultural fields and clear cut areas are occupied firstly by coniferous tree clusters such as Pinus sylvestris and Pinus nigra. Because the seeds of these conifer tree clusters germinate only when exposed to direct solar radiation on mineral soil as it happens on abandoned agricultural fields. So, the coniferous clusters form the initial succession in the broadleaf deciduous forests. But these clusters may well be converted into pure broadleaf deciduous forests after one rotation period because of the fact that the seeds of these conifer trees do not germinate in the shade of forest understory. The cold humid sunny areas, which are found on the mountainous areas of the northern Anatolia, are the natural occurrence areas of scots pine (Pinus sylvestris) forests. Here the seedlings of Abiesnordmanniana growing underneath the Pinus sylvestris forest form a mixed forest of Pinus sylvestris and Abies nordmanniana. This forest is then converted into pure and/or mixed Abies forest in places where Pinus sylvestris has been completely removed. In short, the light factor is the driving force especially in the competition between conifer and broadleaf trees in the cold-humid and cold and mild forest environments of northern Turkey.